Simulation Strategic Positioning for Mobile Robot Roccer Wheels - Bachtiar, Mochamad Mobed; Wibowo, Iwan Kurnianto; Ajie, Rakhmat Faizal (Journal of Applied Informatics and Computing, 2018)
Soccer robot is a combination of sports, robotics technology and multi agent system. The achieve goals in playing the ball, requires individual intelligence, and the ability of cooperation for individual skills. The success of a soccer robot team is influenced by the success of the robot player to enter the ball into the opponent's goal. In entering the ball into the opponent's goal needed an appropriate position and strategic. This research makes the design in finding a strategic position at the time of attack. The design divides the field into several small areas or the main grid, where each region gives different action. The position is said to be strategic if the robot passing success and has a fairly wide perspective against the goal. The strategic position is gained from the greatest opportunity of some of the decisive conditions. The calculation used is to use the Probability Naive Bayes Classifier by taking the maximum value that serve as a strategic position. So this research resulted in a design in finding strategic position.